Multiparidad como factor de riesgo obstétrico y reproductivo en las gestantes atendidas en el Hospital Provincial Martín Icaza, Babahoyo. Noviembre 2023-abril 2024. - Carpio Balladares, Marlen Victoria (2024)
Multiparity is a risk factor during pregnancy, childbirth or the postpartum period; It deals with motherhood and death and other issues that arise during pregnancy. Too much labor causes the uterus to lose its normal shape, the elasticity and contractility of the muscle fibers decreases, so, with labor and birth, the uterus contracts with little force and creates cervical problems, which may be the reason due to prolonged labor, use of oxytocic drugs, retained placenta, soft tears and weak uterine contractions after birth. Therefore, during pregnancy and childbirth, the uterus will contract with little force, causing problems. The level of the cervix, which may be responsible for postpartum hemorrhage from prolonged labor, use of oxytocic drugs, retained placenta, soft tears, and uterine atony. The impact of deaths from multiple births on maternal health has been reported; It is claimed to increase the risk of anemia in the mother and in fact this has been found to mean more frequent births and returning to breastfeeding; Controls the decrease in various micronutrients, especially iron, in pregnant women.